The role of the World Bank in agricultural development in the 1990s - Lipton, Michael; Paarlberg, Robert L. (International Food Policy Research Institute, 1990)
The World Bank' provides about 10 percent of the net aid disbursed and about 15 percent of the officially supported resource flows to developing countries (Organization for Economic Cooperation and Development 1985, 142, 162; 1988, 264-265; World Bank 1988e, 265). Its role in agriculture and rural development (ARD) is even more important? It provided 29 percent of official flows to ARD in fiscal years 1980-83 and 36 percent in 1985. This is almost equal to the total flow of bilateral aid to ARD. In 1979-83, only 16 percent of bilateral aid reached agriculture compared with about 30 percent of Bank flows (World Bank 1988, 214-215; United Nations 1989; Lipton, 1987,3).